Analisis Faktor Faktor Yang Mempengaruhi Produksi Pembenihan Ikan Mas Terhadap Pendapatan Petani (Studi Kasus di Kabupaten Aceh Tenggara) - Ilhamdi, Ilhamdi; Hasnudi, Hasnudi; Harahap, Gustami (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
Â Goldfish is one type of fish that have a fairly high economic value, it contains a lot of protein and cheaper. Fish hatchery is an activity that doing fish hatchery that will be produced fish seed, then followed up with the activities of breeding and growing. This study was carried out in the district of Lawe Bulan and the District Deleng Pokhisen Southeast Aceh district of Aceh province. Where the study area was determined by purposively. The purpose of this study was to analyze the business income of hatchery goldfish and financial feasibility, determining capital influence, large pool, the number of the parent, food seed, the labor against income of farmers seeder carp and analyze the influence of the level of education and experience of the farmers' income carp in the District Southeast Aceh. The sampling method used is the census method that is the entire population of the research sample. Data analysis method used is descriptive analysis method. To test the first hypothesis using Business Analysis, to examine the second hypothesis using analysis of Cobb-Douglas. To test the three hypotheses using Multiple Linear Regression Analysis with SPSS for Windows version 20. The results showed an average net income hatchery operations goldfish is Rp 5.814.200,- per production cycle. In terms of financial feasibility on carp hatchery operations in Southeast Aceh District covers the calculation of R/C ratio of 1.41. PP 4.8. BEP 2620834.0. Thus carp hatchery operations in Southeast Aceh district can provide benefits to farmers and to develop. Cobb-Douglas analyzes the results of each of the factors of production that have a significant effect (positive) is fodder seed (1.002), labor (0.908) and the parent (0.051). While the production factor is capital no significant effect (-0.028) and spacious pool (-0.164). Results Regression analysis of factors affecting skills that the education level (0.032) and experience (0,181).